Treatment Considerations for Obstructive Sleep Apnea in Pediatric Down Syndrome - Erica Gastelum; Marcus Cummins; Amitoj Singh; Michael Montoya; Gino Luis Urbano; Mary Anne Tablizo (MDPI AG, 2021)
Children with Down syndrome (DS) are at high risk for developing obstructive sleep apnea (OSA) compared to children without DS. The negative impact of OSA on health, behavior, and cognitive development in children with DS highlights the importance of timely and effective treatment. Due to the higher prevalence of craniofacial and airway abnormalities, obesity, and hypotonia in patients with DS, residual OSA can still occur after exhausting first-line options. While treatment commonly includes adenotonsillectomy (AT) and continuous positive airway pressure (CPAP) therapy, additional therapy such as medical management and/or adjuvant surgical procedures need to be considered in refractory OSA. Given the significant comorbidities secondary to untreated OSA in children with DS, such as cardiovascular and neurobehavioral consequences, more robust randomized trials in this patient population are needed to produce treatment guidelines separate from those for the general pediatric population of otherwise healthy children with OSA. Further studies are also needed to look at desensitization and optimization of CPAP use in patients with DS and OSA.